2007
DOI: 10.1111/j.1365-2222.2007.02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with peanut allergy recognize predominantly Ara h2 and Ara h6, which remains stable over time

Abstract: Ara h2 and Ara h6 are the most frequently recognized major peanut allergens in children. The individual reactivity to the major peanut allergens remained stable over time, despite DBPCFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 26 publications
13
126
0
Order By: Relevance
“…However, we did not find any differences for anaphylaxis or urticaria/angioedema. Our data agree with previous studies (28,47), although one study has shown anaphylaxis to be more highly associated with Ara h 2 (48).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we did not find any differences for anaphylaxis or urticaria/angioedema. Our data agree with previous studies (28,47), although one study has shown anaphylaxis to be more highly associated with Ara h 2 (48).…”
Section: Discussionsupporting
confidence: 93%
“…In Group B, Ara h 9 and Pru p 3 were significantly higher. These findings agree with other studies (17,18,45,47,50). However, only 22% of cases from Group A had systemic reactions (anaphylaxis and urticaria/angioedema) and only 12% of Ara h 2 positive cases Ara h 2 from Group B had systemic reactions.…”
Section: Discussionsupporting
confidence: 92%
“…Ara h 1, Ara h 2, and Ara h 3 are considered the major peanut allergens (Burks et al, 1998), as well as Ara h 6 in some studies (Flinterman et al, 2007).…”
Section: Identified Allergensmentioning
confidence: 99%
“…Although the protein Ara h 1 (vicilin family) accounts for about 20% of the total peanut proteins, Ara h 2 (conglutin family) constitutes the most frequently recognized allergen in children (Nicolaou et al, 2005;Flinterman et al, 2007). In the present work, an electrochemical genosensor for detection of an 86-mer DNA sequence encoding part of the allergenic protein Ara h 2 from peanut, was developed.…”
Section: Introductionmentioning
confidence: 97%